THE EFFICACY AND SAFETY OF TOPICAL TRIAMCINOLONE IN REDUCING URETHRAL STRICTURE RECURRENCE FOLLOWING INTERNAL URETHROTOMY: A SYSTEMATIC REVIEW AND META-ANALYSIS - Hamzah, Moh. Alwi; Muhammad Risan; Muhammad Jabir (Indonesian Journal of Urology, 2025)
Objective: This systematic review aims to determine the efficacy and safety of topical triamcinolone in reducing urethral stricture recurrence following internal urethrotomy procedures. Material & Methods: A systematic literature search was performed in Cochrane Library, PubMed and Google Scholar with the related keywords. The statistical analysis was conducted using a Review Manager v.5.4.1. Results: We identified 6 RCTs with a total of 316 patients diagnosed with urethral stricture undergoing internal urethrotomy. The statistical analysis appeared to lower the recurrence rate significantly in patients undergoing internal urethrotomy with the adjuvant therapy of topical triamcinolone (RR 0.55, 95% CI 0.38 – 0.78, p = 0.0008). Conclusion: Additional treatment with topical triamcinolone has the benefit of declining the recurrence rate of urethral stricture following internal urethrotomy. Keywords: Triamcinolone, urethral stricture, internal urethrotomy.